Epidemiology of paratuberculosis in wild ruminants studied by restriction fragment length polymorphism in the Czech Republic during the period 1995-1998 - Pavlik, I; Bartl, J; Dvorska, L; Svastova, P; du Maine, R; Machackova, M; Yayo Ayele, W; Horvathova, A (Veterinary microbiology, 2000)
In two studies carried out during the period 1995-1998, paratuberculosis was diagnosed in domestic and wild ruminants in the Czech Republic. The isolated Mycobacterium avium subspecies paratuberculosis strains were analysed by standardised restriction fragment length polymorphism (RFLP) [Pavlik, I., Horvathova, A., Dvorska, L., Bartl, J., Svastova, P., du Maine, R., Rychlik, I., 1999. J. Microbiol. Methods 38, 155-167]. In December 1992, 19 late pregnant Charolais heifers were imported to the Czech Republic from Hungary (original import from France to Hungary). One 11-month-old heifer roamed in the wild in a range of approximately 15-20km for 7 months from November 1993 to May 1994. Upon capture, the animal showed clinical signs of paratuberculosis (emaciation and diarrhoea). Seven other animals from the same herd were infected with the identical RFLP type B-C1 of M. paratuberculosis. During the period 1995-1996, samples were taken and examined from the small intestine and corresponding lymph nodes of 84 wild ruminants: 19 red deers (Cervus elaphus) and 65 roe-deers (Capreolus capreolus). These wild ruminants originated from 44 different locations within the same district from as the infected escaped heifer. Five M. paratuberculosis strains were isolated: one strain of RFLP type B-C1 from a stag and three strains of RFLP type B-C1 and one strain of RFLP type B-C9 from roe-deer. The three wild ruminants (one stag and two roe-deer) infected with the same RFLP type B-C1 were detected in the same area as the heifer, suggesting that this was the likely infection source. However, the infection source of the roe-deer infected with strain of RFLP type B-C9 was obviously different, and the stags that escaped from the farm were purchased from an area infected with this RFLP type. In the second study carried out during 1997-1998 in the whole Czech Republic (divided into 76 districts), 718 wild ruminants were examined from 90% of the districts. M. paratuberculosis was isolated from 25 (3.5%) animals from the wild, from farms and from game parks: 7.1% of 132 red deers, 1.5% of 336 roe-deers, 3.9% of 178 fallow deers (Dama dama), and 4.2% of 48 moufflons (Ovis musimon). This study discovered three RFLP types (B-C1, D-C12 and M-C16). A surprising finding was that of M. paratuberculosis (RFLP type B-C1) infection in roe-deer and a fallow deer in their natural habitat. The infection source was determined to have originated from two imported Holstein and Limousine cattle herds infected with the same strain. In the case of a mother and daughter roe-deer infected with RFLP type M-C16 and a fallow deer infected with RFLP type D-C12, all roaming in their natural habitat, the infection source was not discovered. The highest incidence of clinically ill wild ruminants was found in farmed red deer, and no relationship was found between the RFLP type or ruminant species and clinical status of animal.
Keywords: Deer; vysoká zvěř; divoká zvířata; feces; Paratuberculosis; Polymorphism, Restriction Fragment Length; prevalence; Mycobacterium avium subsp. paratuberculosis; hospodářská zvířata; zvířata; přežvýkavci; Animals, Wild; statistická rozdělení; Feces; Statistical Distributions; paratuberkulóza; Cattle; Animals, Domestic; Czech Republic; skot; Prevalence; Animals; polymorfismus délky restrikčních fragmentů; Česká republika; Ruminants